Trop2-Based Antibody–Drug Conjugates: Emerging Strategy and Progress in Triple-Negative Breast Cancer Therapy. - Li, Tong; Zhang, Tao; Dang, Yongxia; Lin, Yilin; Li, Xiaotong; Ling, Xiaoling (Current Oncology, 2026)
Simple Summary: With the aim of providing evidence-based insights for improved prognosis in TNBC patients, this article conducts a systematic review of the clinical research progress of Trop2-targeted ADCs. Trop2-targeted therapies are set to become a cornerstone of precision medicine for solid tumors, thereby paving the way for superior treatment options for patients. Triple-negative breast cancer (TNBC) accounts for 15–20% of invasive breast cancers and represents a highly heterogeneous, aggressive subtype with poor prognosis and limited treatment options, necessitating the identification of novel therapeutic targets to improve clinical outcomes. Trophoblast cell-surface antigen 2 (Trop2), a calcium signal transducer, is frequently overexpressed in TNBC (approximately 88% of cases) while exhibiting minimal expression in normal tissues. Its overexpression is significantly associated with tumor invasion, metastasis, and unfavorable prognosis. Antibody–drug conjugates (ADCs) targeting Trop2 have demonstrated significant clinical potential. This article systematically reviews the clinical research progress of Trop2-targeted ADCs, aiming to provide evidence-based insights for improving the prognosis of TNBC patients.